West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae) - Grichanov, Igor Ya. (European Journal of Taxonomy, 2013)
A new status (as subgenera of Diostracus Loew, 1861) for Sphyrotarsus Mik, 1874, Lagodechia Negrobov & Tsurikov, 1996 and Ozmena Özdikmen, 2010 stat. nov. is proposed. A new species, Diostracus (Sphyrotarsus) kustovi sp. nov., is described from the Russian Caucasus. The following recombinations (comb. nov.) are also proposed: Diostracus (Sphyrotarsus) argyrostomus (Mik, 1874); D. (S.) caucasicus (Negrobov, 1965); D. (S.) hervebazini (Parent, 1914); D. (S.) hessei (Parent, 1914); D. (S.) hygrophilus (Becker, 1891); D. (S.) leucostomus (Loew, 1861); D. (S.) parenti (Hesse, 1933); D. (Lagodechia) spinulifer Negrobov & Tsurikov, 1988; and D. (Ozmena) stackelbergi (Negrobov, 1965). A key to ten Diostracus species inhabiting the West Palaearctic Region is provided.